Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana yang Mengalami Cuci Otak - I Wayan Dedi Supriadi; Simon Nahak; I Nyoman Gede Sugiartha (Jurnal Analogi Hukum, 2019)
Brainwashing in the world of law is not a new concept. In psychology, the term has been used from time to time in a prisoner of war and religious studies. In the field of criminal law, the accused individuals have been tried though not successfully use brainwashing as criminal defence. This article discusses about how criminal liability against a perpetrator of a criminal offence which has undergone brainwashing before committing the crime and how the criminal sanctions against perpetrators. The aims of research is the first, to know and understand the criminal liability against the perpetrators of the crime are undergoing brainwashing and both to know and understand the criminal sanctions against the perpetrators of criminal acts are undergo brainwashing. This research uses the normative method. The author outlines by explaining how the process of brainwashing going on, particularly in the recruitment of members of terrorism and NII, and then associate the process with the theory of errors, to be able to determine if there is an error in the perpetrator criminal who suffered brain washing, so that based on the principle of geen straf schuld, the offender without may be subject to criminal responsibility. The author also outlines how criminal justice in Indonesia and the United States, addressing the question of brainwashing that emerged in the trial. The result of the discussion was the perpetrator of a criminal offence who had previously undergone brainwashing has error in doing so, so that it may be subject to liability criminal. Cuci otak dalam dunia hukum bukanlah suatu konsep yang baru. Di bidang psikologi, istilah telah digunakan dari waktu ke waktu dalam studi tawanan perang dan keagamaan. Di bidang hukum, terdakwa pidana individu telah mencoba meskipun tidak berhasil menggunakan cuci otak sebagai pembelaan pidana. Artikel ini membahas mengenai bagaimana pertanggungjawaban pidana terhadap seorang pelaku tindak pidana yang telah mengalami cuci otak sebelum melakukan tindak pidana dan bagaimana sanksi pidananya terhadap pelaku. Tujuan dari penelitian ini ini adalah pertama, untuk mengetahui dan memahami pertanggungjawaban pidana pidana terhadap pelaku tindak pidana yang mengalami cuci otak dan dan kedua untuk mengetahui dan memahami sanksi pidana terhadap pelaku tindak pidana yang mengalami cuci otak. Penelitian ini mempergunakan metode normatif. Penulis menjabarkan dengan menjelaskan bagaimana proses cuci otak terjadi, khususnya pada perekrutan anggota terorisme dan NII, lalu mengaitkan proses tersebut dengan teori kesalahan, untuk dapat menentukan apakah terdapat kesalahan dalam pelaku tindak pidana yang mengalami cuci otak, sehingga berdasarkan asas geen straf zonder schuld, pelaku tersebut dapat dimintai pertanggung jawaban pidana. Penulis juga menjabarkan bagaimana peradilan pidana di Indonesia dan Amerika Serikat menyikapi soal cuci otak yang muncul dalam persidangan. Hasil dari pembahasan adalah pelaku tindak pidana yang sebelumnya mengalami cuci otak memiliki kesalahan dalam melakukan hal tersebut, sehingga dapat dimintai pertanggung jawaban pidana.